2016
DOI: 10.1128/mbio.01624-16
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Hemagglutinin Stalk-Specific Antibodies Induce Potent Phagocytosis of Immune Complexes by Neutrophils in an Fc-Dependent Manner

Abstract: Broadly neutralizing antibodies that recognize the conserved hemagglutinin (HA) stalk have emerged as exciting new biotherapeutic tools to combat seasonal and pandemic influenza viruses. Our general understanding of the mechanisms by which stalk-specific antibodies achieve protection is rapidly evolving. It has recently been demonstrated that broadly neutralizing HA stalk-specific IgG antibodies require Fc-Fcγ receptor (FcγR) interactions for optimal protection in vivo. Here we examine the neutrophil effector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 52 publications
6
109
0
Order By: Relevance
“…Antibody‐dependent cellular cytotoxicity responses are reportedly highly cross‐reactive, and avian influenza‐specific ADCC antibodies can be found in healthy unexposed individuals and enriched for the HA stem . In our study, ADCC activity towards conserved NP, cross‐reactive H7‐HA, seasonal HA and NA proteins was boosted by recent H1N1 infection.…”
Section: Discussionmentioning
confidence: 90%
“…Antibody‐dependent cellular cytotoxicity responses are reportedly highly cross‐reactive, and avian influenza‐specific ADCC antibodies can be found in healthy unexposed individuals and enriched for the HA stem . In our study, ADCC activity towards conserved NP, cross‐reactive H7‐HA, seasonal HA and NA proteins was boosted by recent H1N1 infection.…”
Section: Discussionmentioning
confidence: 90%
“…These results suggest that Fc receptors partially contribute to the protection by NA antibodies. In line with the roles of Fc receptors in mediating protection, HA stalk-specific antibodies were shown to induce phagocytosis of immune complexes in a FcR dependent manner [19, 20]. Similarly, Fc receptors were required for M2e immune mediated protection [13].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic comparison of the in vivo protective activity of a panel of anti-influenza mAbs with differential neutralizing potency and breadth revealed that strain-specific, neutralizing mAbs directed against the globular head of the influenza HA confer protective activity without a requirement for FcγR engagement [2931]. In contrast, broadly protective mAbs that target highly conserved influenza epitopes rely on interactions with activating Type I FcγRs to mediate antiviral activity in vivo [2933]. These findings clearly highlight that the broad antiviral activity of these IgG antibodies is achieved not only through the targeting of specific, highly conserved epitopes on HA, but also through their capacity to engage and activate distinct FcγR pathways to confer protective effector functions.…”
Section: Igg Fc Domain Effector Functionsmentioning
confidence: 99%